Magnetic Induction Responses of Jupiter's Ocean Moons Including Effects From Adiabatic Convection. Issue 2 (18th February 2021) - Vance, S. D.; Styczinski, M. J.; Bills, B. G.; Cochrane, C. J.; Soderlund, K. M.; Gómez‐Pérez, N.; Paty, C.
Abstract: Prior analyses of oceanic magnetic induction within Jupiter's large icy moons have assumed uniform electrical conductivity. However, the phase and amplitude responses of the induced fields will be influenced by the natural depth‐dependence of the electrical conductivity. Here, we examine the amplitudes and phase delays for magnetic diffusion in modeled oceans of Europa, Ganymede, and Callisto. For spherically symmetric configurations, we consider thermodynamically consistent interior structures that include realistic electrical conductivity along the oceans' adiabatic temperature profiles. Conductances depend strongly on salinity, especially in the large moons. The induction responses of the adiabatic profiles differ from those of oceans with uniform conductivity set to values at the ice–ocean interface, or to the mean values of the adiabatic profile, by more than 10% for some signals. We also consider motionally induced magnetic fields generated by convective fluid motions within the oceans, which might optimistically be used to infer ocean flows or, pessimistically, act to bias the ocean conductivity inversions. Our upper‐bound scaling estimates suggest this effect may be important at Europa and Ganymede, with a negligible contribution at Callisto. Based on end‐member ocean compositions, we quantify the magnetic induction signals that might be used to infer the oxidation state of Europa's ocean and to investigate stable liquids under high‐pressure ices in Ganymede and Callisto. Fully exploring this parameter space for the sake of planned missions requires thermodynamic and electrical conductivity measurements in fluids at low temperature and to high‐salinity and pressure as well as modeling of motional induction responses. Plain Language Summary: Oscillations in a planet's magnetic fields can create magnetic signals within its companion moons if those moons have salty oceans under their icy surfaces. Fluid currents within those oceans can also create magnetic fields. Spacecraft investigating those oceans can measure such fields and thereby learn about the properties of the oceans. We compute possible magnetic properties for Jupiter's ocean moons—Europa, Ganymede, and Callisto—using available chemical data and electrical conductivity. Previous work has also computed these properties, but our methods allow us to account for how the electrical properties vary with depth due to pressure and temperature. We also model ocean currents. We find that the depth‐dependence of electrical conductivity affects the predicted magnetic fields more than 1 nT as compared with the typical assumption of a uniform conductivity. This is important because the planned Europa Clipper and JUpiter ICy moons Explorer (JUICE) missions will measure magnetic fields at these moons with roughly 1 nT precision. For Europa, we examine seawater (NaCl) and MgSO4 ocean compositions linked to more hydrogen‐rich or oxygen‐rich scenarios. With additional constraints on ice shell and ocean thickness from other spacecraft measurements, magnetic measurements may be a key tool for determining the composition of Europa's ocean, and thus its chemical evolution through time. Key Points: The signal from induction that accounts for adiabatic ocean temperatures is distinct from induction based on uniform conductivity Motional induction due to thermal convection in the satellite oceans may be significant Material properties and motional induction modeling are needed to obtain ocean composition from magnetic induction